Cardiac arrest and drug-related cardiac toxicity in the Covid-19 era. Epidemiology, pathophysiology and management. (November 2020) - Mavraganis, Georgios; Aivalioti, Evmorfia; Chatzidou, Sofia; Patras, Raphael; Paraskevaidis, Ioannis; Kanakakis, Ioannis; Stamatelopoulos, Kimon; Dimopoulos, Meletios-Athanasios
Abstract: SARS-CoV-2 (Covid-19) infection has recently become a worldwide challenge with dramatic global economic and health consequences. As the pandemic is still spreading, new data concerning Covid-19 complications and related mechanisms become increasingly available. Accumulating data suggest that the incidence of cardiac arrest and its outcome are adversely affected during the Covid-19 period. This may be further exacerbated by drug-related cardiac toxicity of Covid-19 treatment regimens. Elucidating the underlying mechanisms that lead to Covid-19 associated cardiac arrest is imperative, not only in order to improve its effective management but also to maximize preventive measures. Herein we discuss available epidemiological data on cardiac arrest during the Covid-19 pandemic as well as possible associated causes and pathophysiological mechanisms and highlight gaps in evidence warranting further investigation. The risk of transmission during cardiopulmonary resuscitation (CPR) is also discussed in this review. Finally, we summarize currently recommended guidelines on CPR for Covid-19 patients including CPR in patients with cardiac arrest due to suspected drug-related cardiac toxicity in an effort to underscore the most important common points and discuss discrepancies proposed by established international societies. Highlights: Covid-19 pandemic is associated with increased incidence of cardiac arrest. Cardiac, non-cardiac causes and drug-related toxicity may jointly contribute to cardiac arrest associated with Covid-19. Recommendations for cardiac arrest management are modified during the pandemic. Recommendations for prevention and management of drug-related toxicity related to Covid-19 are summarized.